Demonstration of Gd-GEM detector design for neutron macromolecular crystallography applications. (1st April 2023) - Pfeiffer, D.; Brunbauer, F.; Cristiglio, V.; Hall-Wilton, R.; Lupberger, M.; Markó, M.; Muller, H.; Oksanen, E.; Oliveri, E.; Ropelewski, L.; Rusu, A.; Samarati, J.; et al.
Abstract: The European Spallation Source (ESS) in Lund, Sweden will become the world's most powerful thermal neutron source. The Macromolecular Diffractometer (NMX) at the ESS requires three 51.2 × 51.2 cm 2 detectors with reasonable detection efficiency, sub-mm spatial resolution, a narrow point-spread function (PSF), and good time resolution. This work presents measurements with the improved version of the NMX detector prototype consisting of a Triple-GEM (Gas Electron Multiplier) detector with a natural Gd converter and a low material budget readout. The detector was successfully tested at the neutron reactor of the Budapest Neutron Centre (BNC) and the D16 instrument at the Institut Laue-Langevin (ILL) in Grenoble. The measurements with Cadmium and Gadolinium masks in Budapest demonstrate that the point-spread function of the detector lacks long tails that could impede the measurement of diffraction spot intensities. On the D16 instrument at ILL, diffraction spots from Triose phosphate isomerase w/ 2-phosphoglycolate (PGA) inhibitor were measured both in the MILAND Helium-3 detector and the Gd-GEM. The comparison between the two detectors shows a similar point-spread function in both detectors, and the expected efficiency ratio compared to the Helium-3 detector. Both measurements together thus give good indications that the Gd-GEM detector fits the requirements for the NMX instrument at ESS.